Egg Production of Local Merawangarab with Different Genetic Composition - Nurwansyah, Rafif; Darwati, Sri; Nurcahya, Harini (Universitas Nasional Jakarta, 2024)
Chicken eggs are the most widely consumed poultry product. Eggs have high protein value and are affordable for the public. Demand for local chicken eggs continues to increase every year. Merawang chicken and Arabian chicken are local Indonesian chickens. It is hoped that crossing the two chickens will produce superior offspring in egg production. The research was conducted to evaluate egg production in local chickens of the merawangarab cross with different genetic compositions of the merawang (M), namely 25% M, 50% M, 62.5% M, and 75% M, totaling 31 birds consisting of 21 adult females and 10 males. This research used a randomized block design (RAK). Egg production has achieved quite good results. The genetic composition affected egg index (P<0.05), but egg weight, hen day production, and feed conversion were the same. The four types of merawangarab chickens have the potential to be local egg-producing chickens. The egg production performance of 25%M, 50%M, 62.5%M, and 75%M was the same and all four could be developed as local laying hens.